Sustainable Human Resources in the Tourism Industry in Indonesia: Employee Competence and Government Regulation - Hendriati, Yossi; Sya'rani, Ridwan (International Journal of Business, Law, and Education, 2024)
The present study investigates the dynamics of sustainable human resources (HR) practices in the Indonesian tourist sector, with a particular emphasis on staff skills and adherence to government rules. The study utilized a quantitative methodology, specifically utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS), to examine data gathered from 235 individuals who represented a varied range of industries. The findings showed strong positive correlations: employee capabilities and compliance with legal requirements are both positively impacted by sustainable HR practices. Furthermore, compliance with government rules is positively impacted by staff competencies. With a Root Mean Square Error of Approximation of 0.06 and a Goodness-of-Fit Index of 0.92, the model demonstrated a decent fit. These results provide important new understandings of the complex interactions that exist in the Indonesian tourism industry between employee capabilities, sustainable HR practices, and regulatory compliance.